Implementasi Program Market Day untuk Menumbuhkan Karakter Kewirausahaan Santri Kuttab - Yulianto, Arvani; Bakri, Syamsul (ISLAMIKA, 2024)
The purpose of this research is to analyze the implementation of the market day program in fostering entrepreneurial character among the students of Kuttab Al Faruq Sukoharjo, as well as the factors that support and hinder its implementation. The research method employed is qualitative case study. The research informants include teachers, students, and guardians of the Kuttab students. Data collection was conducted through observation, interviews, and documentation. Data analysis technique utilized qualitative data analysis with an interactive model. The findings of the research indicate that the market day program at Kuttab Al Faruq can foster entrepreneurial character among the students, from the planning stage to implementation and evaluation. The entrepreneurial character traits developed among the students include self-confidence, independence, teamwork, and problem-solving skills. The supporting factors for the implementation of market day include educator involvement, active participation from guardians, enthusiasm from students, and the availability of school facilities. The hindering factors for the implementation of market day include lack of trading experience and difficulty in devising marketing strategies.